Antispasmodic activities of the methanolic extract from aerial parts of Origanum species on excised rat ileum - (:unkn) unknown (ISTANBUL UNIV, FAC PHARMACY, 2020)
Background and Aims: Origanum hypericifolium, Origanum minutiflorum, Origanum saccatum, and Origanum haussknechtii are some of the endemic Origanum species in Turkey. In the literature, besides the known effects of these Origanum species, no antispasmodic activity was determined. Therefore, we investigated Origanum species for possible antispasmodic effects to rationalize its traditional medicinal use. The present study aimed to investigate the antispasmodic activity of Origanum species with the organ bath. Methods: Rats were divided into 5 groups. While no treatment was given to the control group, plant extracts were given to other groups. Real tissues taken by rats were used for evaluating the contraction responses elicited with potassium chloride (KCl) and acetylcholine (ACh). Thereafter, the extracts of Origanum species were applied and cumulative concentration-response curves of these species were constructed in each experiment. Results: All treatments with Origanum species have a relaxation effect on rat ileum as compared with the control group. According to the results of the isolated organ bath study, KCl and ACh-induced ileum contractions were significantly decreased by all Origanum species. Conclusion: Origanum species that were used in the present study can prevent smooth muscle contraction of ileum, and therefore they can be used to reduce intestinal spasms.
Keywords: Origanum hypericifolium; Origanum minutiflorum; Origanum saccatum; Origanum haussknechtii; Organ bath; Antispasmodic effect; PRAECOX SUBSP SKORPILII; ESSENTIAL OIL; ANTIOXIDANT